TRANSFER PENGETAHUAN MELALUI MEDIA SOSIAL OLEH STAF AHLI ANGGOTA LEMBAGA NEGARA MAHARDHIKA - Kartika Adelia, Melly; Laksmi, Laksmi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
This research seeks to understand the process of action of expert staff of Legislative Assembly of Mahardhika in fulfilling its duties and functions namely decision making by considering public opinion, as well as a means of building the image of member of state in expressing itself personally and institution. This research uses case study method with qualitative approach. Informants were determined based on purposive sampling method and obtained five people. The results of this study indicate that in the knowledge transfer through social media in the Legislative Assembly of Mahardhika done based on the understanding of the team of expert staff that social media is associated with the concept of the corporation or organization which is interpreted as a medium that has the purpose to provide information to the public in accordance with the existing moment, while the purpose of using social media by expert staff is more aimed at reaches the wider community. The application of knowledge transfer by expert staff through social media is done in five steps, namely intermediation, externalization, internalization, cognitive, and evaluation. The intermediation step, ie matching efforts between the communication agenda and the existing subject trend, is the most important and sustainable step. Social media that is the most effective in disseminating information to the public is Facebook, followed by Twitter and Instagram.